O deslocamento do sujeito : a saga identitária em Hotel Atlântico de João Gilberto Noll - Caliari, Janice Soares (2014)
The objective of this research is to analyze the identity issue in the novel Hotel Atlantic, written by João Gilberto Noll, following the trajectory of the wandering narrator-character, an individual who moves adrift, against the grain of society, seeking new circumstances that allow him to experience the possibility of being another one, using masks that represent different identities. Noll brings out in the literary scene, the representation of the fragmentation, the restlessness and loneliness, characteristics of postmodern man and his troubled relation ship with time. When creating a language that projects distorted images in time and space, the gaucho writer seeks to promote reflection and questioning about the feeling of insecurity and weirdness experienced by individuals in the ephemeral and decentralized world of postmodernity. To expound this complex and provisory topic that the identity is, it will be fundamental the Stuart Hall’s considerations and the approaches of Zygmunt Bauman who, when referring to the liquid-modern world, shows how the identity has become a necessary subject for understanding of the social transformations and its implications in the personal individuality.